Design and Development of a Geographic Information System for Mapping the Distribution of Non-Communicable Diseases Using the Agile Method - Rahmah, Anindita Hasniati; Kawuri, Gabriella Vindy; Alfiyani, Lina; Septiani, Yunita Ayu (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
The prevalence of non-communicable diseases (NCDs) continues to increase and poses a significant public health challenge. The impacts include premature mortality and long-term disability. Effective monitoring and spatial analysis are needed to support timely and accurate interventions in managing NCD cases. This study aimed to design and develop a Geographic Information System (GIS) for mapping the distribution of non-communicable diseases using the Agile development method. This study employed the Agile method, which consists of six phases: requirements, design, development, testing, deployment, and review. The research utilized a mixed-method approach, combining quantitative and qualitative data, with secondary data used as the primary data source. The findings indicated a consistent spatial pattern in which heart disease, stroke, and hypertension cases tended to cluster in subdistrict centers or densely populated villages. In contrast, diabetes mellitus cases were more widely distributed across the region, including both central and peripheral rural areas. Hypertension cases were frequently located near heart disease and stroke cases. Most clusters of non-communicable diseases were found around main roads and public service centers, suggesting that residential density and accessibility are associated with the distribution of cases. However, the spread of diabetes into rural areas indicates that non-communicable diseases are not only an urban issue but are increasingly expanding into rural communities. In conclusion, the developed GIS successfully identified spatial patterns of non-communicable disease distribution and can serve as a useful tool to support rapid and accurate public health interventions.Keywords: agile method; geographic information system; mapping; non-communicable diseases; system design